Synthesis and characterization of oxygen depleted tert-amine calix[4]arene ligands and study the effect on sigma non-opioid intracellular protein receptor - Chaturvedi N.; Mishra A.; Rawat V. (My University, 2025)
This study focuses on the biological prospects of oxygen-depleted calix[4]arene ligands on a protein target. Because of their extensive medical relevance, the oxygen-depleted bis(piperdine) (BPD) and bis(pyrazole) (BPZ) ligands were synthesized and characterized by NMR and mass spectrometry. Furthermore, molecular docking followed by molecular dynamics simulation was utilized to understand the behavior of ligands on selection of sigma non-opiod intracellular receptor (SigNOR) as a suitable protein target. The simulations were carried out by three level of complexity: (1) Apo SigNOR, (2) BPD: SigNOR, and (3) BPZ: SigNOR. The three complex systems were subjected to stability check before detail analysis. From the results of the estimation of binding free energy, it follows that both ligands possess the same free energy of binding which, in turn, suggests their similar role; however, energy components such as Van der waal and electrostatic potential recommend BPZ were identified as a competitive drug on SigNOR. In addition, temporal distribution of the clusters suggests that scattering of the cluster’s popularity is a measure of fast structural transitions in both complexes. Current study utilizes modern approach to synthesis, characterization, and simulation of our ligands. This study appropriately highlights the effect of our ligands on SigNOR Protein, which might further be extended to potential in vitro and in vivo bioassay. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.